2017
DOI: 10.1111/add.13923
|View full text |Cite
|
Sign up to set email alerts
|

Structural neuroimaging correlates of alcohol and cannabis use in adolescents and adults

Abstract: Background and Aims Chronic alcohol use is associated with lower gray matter volume, and we recently reported that alcohol use showed negative associations with widespread gray matter (GM) volume even among young adults. The current study aimed to test the strength of association between (1) alcohol use and GM volume; (2) alcohol use and white matter (WM) integrity; (3) cannabis use and GM volume; and (4) cannabis use and WM integrity among adults and adolescents. Design and Setting General linear models wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 75 publications
3
27
0
3
Order By: Relevance
“…For example, Weiland and colleagues [17] compared 50 adolescent daily users of cannabis to 50 demographically matched non-users, replicating methods from an earlier study [49], and found non-significant differences in volume, surface-based morphometry, and shape. Similarly, in a sample of 439 adolescents, Thayer and colleagues [54] found no significant associations of past month cannabis use with brain volume or measures of diffusivity after covarying for alcohol use disorder symptoms. Our results extend these studies by probing effects across levels of cannabis use and examining measures of cortical thickness and gray matter density.…”
Section: Discussionmentioning
confidence: 94%
“…For example, Weiland and colleagues [17] compared 50 adolescent daily users of cannabis to 50 demographically matched non-users, replicating methods from an earlier study [49], and found non-significant differences in volume, surface-based morphometry, and shape. Similarly, in a sample of 439 adolescents, Thayer and colleagues [54] found no significant associations of past month cannabis use with brain volume or measures of diffusivity after covarying for alcohol use disorder symptoms. Our results extend these studies by probing effects across levels of cannabis use and examining measures of cortical thickness and gray matter density.…”
Section: Discussionmentioning
confidence: 94%
“…The main changes for use in the year involved increased use of inhalants and cocaine. 9 There are studies that show evidence that prolonged use of cannabis may cause cognitive and motor impairment 5,[15][16] or deficits in social skills. 17 From a literature review on the effects of cannabis on executive functions, an evidence-based study found that there is an interesting pattern of recovery of some functions, as well as the persistence of other deficits.…”
Section: /14mentioning
confidence: 99%
“…On the other hand, a British study suggests that there are no structural changes in the brains of chronic users of cannabis, whether adults or adolescents. 16 The use of cannabis impairs acute inhibition and promotes impulsivity; during abstinence, these deficits are more evident in tasks that require conceptual training, planning, and sequencing skills. Working memory is significantly impaired after acute exposure to cannabis, but these deficits may disappear with sustained abstinence.…”
Section: /14mentioning
confidence: 99%
“…[9][10] Onset of cannabis use among adolescents is of particular concern due to the increased risk of harm to this age group. 4 Some of these concerns include the use of other drugs and drug dependency, [11][12] a risk of heavy dependency, 13 lung and respiratory problems, [14][15] memory and attention impairments, 12,[15][16][17][18][19][20][21] a decrease in cognitive capacity related to the process of learning, such as attention, concentration, ranking, visual-spatial integration, immediate retention, and visual memory, [21][22] psychosocial development problems and mental health problems, [23][24] poorer cognitive performance associated with early initiation and persistent use between the early teenage years and adulthood, 4,[23][24][25] and an increase in car accidents associated with acute cannabis use. [26][27][28][29][30] The evidence about potential harms of cannabis use is not conclusive and inconsistencies appear among studies.…”
Section: Introductionmentioning
confidence: 99%